Pushing the doors open: Nonviolent action and inclusion in peace negotiations. (January 2023) - Nilsson, Desirée; Svensson, Isak
Whereas previous research shows that peace agreements which include a broad segment of society are more likely to lead to sustainable peace, little effort has gone into explaining inclusion itself. We address this gap in the literature by providing the first large-N study to examine the causes of inclusive peace negotiations across civil wars. We argue that civil society actors can gain leverage through mobilization of civilian protest, or build trust through dialogue efforts, thereby enhancing the chances of inclusion of non-warring actors at the negotiation table. The argument is examined by analysing unique and new monthly data on peacemaking efforts in all intrastate armed conflicts in Africa and the Americas, 1989–2018, including measures beyond mere nominal participation, such as whether civil society actors or political parties had substantive roles as either mediators or full participants at the peace talks. Our findings show that protests by civil society actors increase the likelihood that non-warring actors will have a seat at the negotiation table, whereas we find no such effect concerning dialogue efforts. The article contributes by providing new insights into how nonviolent action can shape peace processes by opening the doors to negotiations and is thus part of an emerging research agenda that seeks to bring together the fields of civil resistance and inclusive peace processes.